Statistical Analysis of Silver Coinage and Greek Pottery as Economic Indicators in Archaic and Classical Cyprus - Kushnet , Marvin W. (KOINON: The International Journal of Classical Numismatic Studies, 2024)
This paper deals with two classes of ancient artifacts pertaining to the Cypriot city-kingdoms, namely silver coinage and imported Greek pottery. The investigation surveys the period beginning in the late 6th century, when coinage was first employed on Cyprus, down to 332 BC, when the island lost its autonomy to Macedonian control. The conclusions derived from this research are based on statistical analysis of the numismatic and ceramic data, and in many instances serve to uphold and underscore the work of previous researchers who were compelled to rely on smaller sample sizes, extrapolation and intuition. The analysis clearly delineates the movement of Greek pottery to Cyprus prior to, during and after the Peloponnesian War, and tabulates the types of pottery relative to the dates of transit. The movement of Cypriot coinage is also described, and hoard composition is analyzed in an attempt to assess political and trade alliances.